2009
DOI: 10.1124/jpet.109.157461
|View full text |Cite
|
Sign up to set email alerts
|

Brain AT1Angiotensin Receptor Subtype Binding: Importance of Peptidase Inhibition for Identification of Angiotensin II as Its Endogenous Ligand

Abstract: The existence and localization of brain angiotensin receptors is well established. However, questions regarding the endogenous ligand for brain angiotensin type 1 (AT 1 ) receptors necessitates re-examination of brain angiotensin receptor binding studies. To assess the ability of angiotensin II to bind to the brain AT 1 receptor, radioligand binding studies of rat brain AT 1 receptors were performed using both 125 I-angiotensin II and 125 I-sarcosine 1 , isoleucine 8 angiotensin II. Determination of binding ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 37 publications
(45 reference statements)
0
11
0
Order By: Relevance
“…In addition, there were no differences in Ang II, its aminopeptidase-resistant analogs, and Ang III initial peak pressor responses, findings that do not support a requisite formation of Ang III to elicit a response. It has also been established that 125 I-Ang II can bind to brain AT 1 receptors, an effect that does not require conversion to 125 I-Ang III [28]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there were no differences in Ang II, its aminopeptidase-resistant analogs, and Ang III initial peak pressor responses, findings that do not support a requisite formation of Ang III to elicit a response. It has also been established that 125 I-Ang II can bind to brain AT 1 receptors, an effect that does not require conversion to 125 I-Ang III [28]. …”
Section: Discussionmentioning
confidence: 99%
“…AMA was selected since it is an APA inhibitor that is used by many investigators to study Ang II metabolism [26]. GluP was selected since it has recently received much attention as a direct APA inhibitor with a better selectivity for APA [28]. This enzyme was selected as a target for inhibition since it is the major enzyme involved in Ang II conversion to Ang III [26, 29].…”
Section: Discussionmentioning
confidence: 99%
“…The same group indeed subsequently showed that Ang II is an agonist for the rat brain AT 1 receptor and does not require prior conversion to Ang III [138].…”
Section: Angiotensin III and Angiotensin Ivmentioning
confidence: 94%
“…Five of the slides from each set were then incubated in AM5 buffer containing a concentration of 125 I-SI Ang II ranging from 80 pM to 1900 pM in the presence of 10 μM PD123319 (a selective non-peptide AT 2 receptor antagonist) for 120 minutes. Under these conditions, all specific 125 I-SI Ang II binding is at the AT 1 receptor (Karamyan et al, 2009). The sixth slide from each set was incubated with 1900 pM 125 I-SI Ang II in the presence of an AT 1 receptor saturating concentration (3 μM) of Ang II for 120 minutes to determine non-specific binding of 125 I-SI Ang II.…”
Section: Methodsmentioning
confidence: 99%